Efektivitas Ikan Asin, Limbah Ikan dan Umpan Alami Sebagai Umpan Lalat pada Perangkap Lalat Ramah Lingkungan (Eksperimen Lapangan di Kandang Ternak Rumah Pemotongan Hewan Pegirian Surabaya Tahun 2022) - Vena Mega Setyowati; Winarko Winarko; Irwan Sulistio (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2022)
Density of flies was a health problem that must be controlled so as not to cause health problems. One of the control methods was by physically controlling using ecofriendly flytrap with organic bait, namely fish waste, which is a salted fish and natural bait. The research objective was to analyze the effectiveness of fish waste, salted fish, and natural bait as fly bait on ecofriendly flytrap. This type of research is quasi-experimental using the post test group design. The results of the data were based on the calculation of the number of flies and measurements of physical environmental factors in the field for 9 days. Then, the data were analyzed using the Kruskall Wallis statistical test with α of 5%. The results showed that fish waste bait attracted more flies than salted fish bait and natural bait, while statistical tests showed that there were differences in the number of flies caught in fly traps with various baits according to the hypothesis, namely p value <0.05. Fish waste was effectively used as bait in an ecofriendly flytrap.